2020
DOI: 10.1055/s-0040-1702185
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Graft Function following MPFL Reconstruction: A Dynamic Simulation Study

Abstract: Medial patellofemoral ligament (MPFL) reconstruction is currently the primary surgical procedure for treating recurrent lateral patellar instability. The understanding of graft function has largely been based on studies performed with normal knees. The current study was performed to characterize graft function following MPFL reconstruction, focusing on the influence of pathologic anatomy on graft tension, variations with knee flexion, and the influence on patellar tracking. Knee squatting was simulated with 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Simulated patterns of patellar tracking were similar to those determined from the subjects, with peak lateral tracking near full extension 25 . One study showed root mean square errors for simulated lateral patellar shift and tilt of 2.5 mm and 4.0°, respectively 19 . Simulations also produced correlations between trochlear groove depth and patellar tracking similar to those determined from the subjects 26 .…”
Section: Methodsmentioning
confidence: 54%
See 4 more Smart Citations
“…Simulated patterns of patellar tracking were similar to those determined from the subjects, with peak lateral tracking near full extension 25 . One study showed root mean square errors for simulated lateral patellar shift and tilt of 2.5 mm and 4.0°, respectively 19 . Simulations also produced correlations between trochlear groove depth and patellar tracking similar to those determined from the subjects 26 .…”
Section: Methodsmentioning
confidence: 54%
“…25 One study showed root mean square errors for simulated lateral patellar shift and tilt of 2.5 mm and 4.0°, respectively. 19 Simulations also produced correlations between trochlear groove depth and patellar tracking similar to those determined from the subjects. 26 The simulated contact pressure patterns were also similar to those determined from reconstruction of the diagnostic imaging.…”
Section: Computational Models Of Subjectsmentioning
confidence: 68%
See 3 more Smart Citations